444PThe prophylactic effect of 0.1% fluorometholone eye drops on eye disorders caused by high-dose cytarabine. (24th November 2019) - Tsuchiya, T; Kume, T; Akiyama, K; Yoshitsugu, K; Fukaya, M; Enami, T; Tatara, R; Shino, M; Ikeda, T
Abstract: Background: High-dose cytarabine (HDAC) is used to treat hematologic malignancies. Eye disorders are common side effects caused by cytarabine (AraC) being transported from the blood into tear fluid. In our institution, four times a day (FM4) or six times a day (FM6) of 0.1% fluorometholone eye drops are used to prevent AraC-induced eye disorders. In this study, we investigated the prophylactic effects of FM6 or FM4 to prevent AraC-induced eye disorders retrospectively. Methods: We targeted the patients who were hospitalized and administered with HDAC twice a day at a dose of 1 g/m 2 or more between April 2011 and March 2018. The patients received 0.1% fluorometholone eye drops in a both eyes from the start of HDAC dose to 48 hours after the end of HDAC dose. We investigated the incidence of eye disorders or grade based on the medical records from the start of HDAC dose until 7 days after the end of HDAC dose, retrospectively. Results: There were 36 patients of FM4 and 44 of FM6 for prevention of AraC-induced eye disorders, respectivity. The incidence of eye disorders was 6 (16.7%) in FM4 and 7 (15.9%) in FM6. No Grade 3 eye disorders occurred in both groups. The number of courses of the eye disorder appeared for FM4 and FM6 were 1 and 2 courses. In addition, the median of AraC cumulative dose at the time of the eye disorders appeared for FM4 and FM6 was 10 (4-20) g/m 2 and 20 (6-42) g/m 2 . Conclusions: There is no difference in preventive effect between FM4 and FM6 for AraC-induced eye disorders. Further, FM4 is considered useful and a convenient method for the prevention of AraC-induced eye disorders. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.